Increased visceral fat volume raises the risk for recurrence of hepatocellular carcinoma after curative treatment - Imai, Kenji (Oncotarget, 2018)
Obesity is a risk factor for the development of hepatocellular carcinoma (HCC). This study aimed to assess the influence of visceral fat on the recurrence of HCC after curative treatment. In 207 curative cases of HCC, the cross-sectional areas of visceral and subcutaneous fat mass on the computed tomographic image at the fourth lumbar vertebra were normalized by the square of the height to obtain the visceral fat mass index (VFMI) and the subcutaneous fat mass index (SFMI), respectively. Whether VFMI and SFMI contributed to recurrence of HCC and overall survival was analyzed using a Cox proportional hazards model. Increased VFMI was significantly associated with recurrence of HCC (P = 0.006), whereas SFMI was not (P = 0.502). When the patients were divided based on the optimal cut off value for VFMI (47.2 cm(2)/m(2)), obtained from maximally selected rank statistics to best predict the risk for recurrence, the higher VFMI group (n = 79) had more probability of recurrence than the lower VFMI group (n = 128) (log rank test, P = 0.002). There were significant differences in body mass index (P < .0001), SFMI (P < .0001), L3 skeletal muscle index (P < .0001), platelet count (P = 0.003), hemoglobin A1c (P < .0001), triglycerides (P = 0.004), serum leptin (P = 0.043), and underlying liver disease (P < .0001) between the groups. Neither VFMI (P = 0.689) nor SFMI (P = 0.117) significantly contributed to overall survival. VFMI, which is involved in obesity and its related metabolic disorders such as diabetes, hyperlipidemia, and adipokine imbalance, is an extremely promising indicator that can predict the risk of recurrence of HCC after curative treatment.